Merombak Struktur, Membentuk Kultur (Studi Pemikiran Siti Musdah Mulia) - Suriansyah, Eka (Jurnal Studi Agama dan Masyarakat, 2017)
Law is a structure in society that can lead to the formation of a culture. The formation of culture is closely related to the legal system existing in society. Similarly, marriage culture that occurs in society is the result of the formation of a legal structure. In Indonesia, the legal structure of marriage is based on the Marriage Act No. 1 year 1974 and Presidential Instruction No. 1 year 1991 on the Compilation of Islamic Law. These two legal products are controlling the pattern of marriage rules in Indonesia. As time goes by, both products require refinement because of the emergence of the existing of various cases. For example, unregistered marriage that is considered by some people to be the legality of affair where it is due to lack of firmness in the mechanism of marriage recording. Responding to this phenomenon, Musdah Mulia, as an academician, tried to formulate Counter Legal Draft of Compilation of Islamic Law as a form of participating in solving community problems which gradually became a negative culture for the nation.